Extensive Reading and How to Get Them to Do it! - Robb, Thomas (CIEX JOURNAL, 2017)
“I tried Extensive Reading, but my students will not read!” is a frequent lament of teachers. By analogy, if you have a car, it will not work as expected unless the engine is tuned well, the brakes are in good condition and there is petrol in the tank. Extensive Reading (“ER”) is similar. The conditions for encouraging students to read need to be optimal, or the result may be nil. Is there petrol in your students’ tank?